1977
DOI: 10.1002/ijc.2910190210
|View full text |Cite
|
Sign up to set email alerts
|

Murine sarcoma virus (msv)‐induced tumors in mice. I. Distribution of msv‐immune cytolytic t lymphocytes in vivo

Abstract: Quantitative studies using a 51Cr release assay were performed to analyse the time-course of appearance and specificity of cytolytic cells in C57Bl/6 mice inoculated with Moloney murine sarcoma virus (MSV). Various lymphoid organs were studied including spleen, mesenteric lymph nodes (MLN), lymph nodes regional to the MSV-induced tumor (RLN), and peripheral blood. Furthermore, the kinetics of appearance of cytolytic cells within the MSV-induced tumor was determined. In agreement with previous studied, it was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Similarly the carcinomas of the cervix uteri, skin and lip may be linked to papilloma viruses [46]. Virally transformed cells may be strongly antigenic [33,41,71]. It is reasonable to assume that these antigenic tumour cells can cause an immune reaction that induces CTLs which kill these virally induced tumour cells in the healthy person.…”
Section: Resistance Against Spontaneously De Novo Arising Tumour Cellsmentioning
confidence: 99%
“…Similarly the carcinomas of the cervix uteri, skin and lip may be linked to papilloma viruses [46]. Virally transformed cells may be strongly antigenic [33,41,71]. It is reasonable to assume that these antigenic tumour cells can cause an immune reaction that induces CTLs which kill these virally induced tumour cells in the healthy person.…”
Section: Resistance Against Spontaneously De Novo Arising Tumour Cellsmentioning
confidence: 99%
“…Cytotoxic activity associated with spleen cells from animals undergoing regression of an autochthonous or a syngeneic tumor as well as those immunized with syngeneic tumors is often not detectable, or very low if detected [4,6,8,9,14,15,20]. Nevertheless substantial cytotoxic activities are often developed at the site of the regressing tumor or of tumor immunization [4,8,14,20].…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratories have tried to relate the systemic studies to the host response within the tumour, in an attempt to identify the important effector mechanisms responsible for regression. Cytotoxic T cells (Plata & Sordat, 1977;Holden et al, 1976;Gillespie et al, 1977;Chapdelaine et al, 1979), cytolytic macrophages and cytostatic macrophages (Puccetti & Holden, 1979;Russell et al, 1977) have been isolated from enzymedispersed tumours induced both by MSV and by the MSC tumour line established from an MSV-induced sarcoma. Studies carried out on both systemic and intratumoral immunity to MSV in A/Sn mice, however, indicated that cytotoxic T cells are not induced in this strain, suggesting that cytotoxic T cells might not be essential for the regression of MSV-induced tumours (Becker & Klein, 1976.…”
Section: Discussionmentioning
confidence: 99%
“…It has been classified as a true malignancy (Perk & Moloney, 1966) as well as a reparative granulomatous process (Stanton et al, 1968;Siegler, 1970). The regression of the lesion is T-cell-dependent Gorezynski, 1974;Stutman, 1.975) and cytotoxic T cells have been found in lymphoid organs and blood as well as within the tumour mass in C57BL and BALB/c mice (Plata & Sordat, 1977;Holden et al, 1976;Gillespie et al, 1977). Thus cytotoxic T cells are considered to play an important role in regression.…”
mentioning
confidence: 99%
See 1 more Smart Citation